POETIC METAPHORS OF LOVE IN ENGLISH AND VIETNAMESE - Phan Van Hoa (VNU Journal of Foreign Studies, 2023)
The conceptual metaphor theory states that poetic metaphors are in fact conventional metaphors but they are made novel via four techniques - elaboration, extending, questioning, and combination. Based on this sense, our paper focuses on examining and comparing poetic metaphors of romantic love in English to those in Vietnamese. Contrastive analysis is the main method applied in the study with the data for investigation coming from English and Vietnamese love poems. Also, the metaphor identification procedures by Pragglejaz Group and its extension are employed to minimize the risk of impulsiveness in metaphor collection process. Our findings reveal that the novelty of love metaphors in poetry does not lie in concepts but in linguistic expressions thanks to the four above techniques, among which combination is employed much more than the others in both languages. Furthermore, both conceptual and linguistic metaphors of love are found to be similar between English and Vietnamese poetry, which is supposed to result from the universality of metaphor. However, variations of cultures, lifestyles, and thought bring about some differences of love metaphors between these two languages